2011
DOI: 10.2460/ajvr.72.4.578
|View full text |Cite
|
Sign up to set email alerts
|

Urodynamic evaluation of female cats with idiopathic cystitis

Abstract: Objective To compare values of urodynamic measurements of cats with idiopathic cystitis (IC) with previously published data for healthy female cats. Animals 11 female cats with IC. Procedures 2 sequential cystometrograms and 2 urethral pressure profiles were obtained for each cat. All tracings were evaluated for evidence of overactive urinary bladder (OAB). Maximum urethral pressure (MUP), maximum urethral closure pressure (MUCP), and functional profile length were recorded. Results Only 3 cats had obvio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Increased sensitivity of mucosal muscarinic receptors (Ikeda and others 2009), although no evidence of an overactive bladder (Wu and others 2011) ;…”
Section: Pathogenesis Of Feline Idiopathic Cystitismentioning
confidence: 99%
See 1 more Smart Citation
“…Increased sensitivity of mucosal muscarinic receptors (Ikeda and others 2009), although no evidence of an overactive bladder (Wu and others 2011) ;…”
Section: Pathogenesis Of Feline Idiopathic Cystitismentioning
confidence: 99%
“…Propantheline: This anticholinergic has been proposed to help with urge incontinence associated with FIC, but in fact there is no evidence that FIC is associated with an overactive bladder (Wu and others 2011). One short-term controlled study of propantheline did not demonstrate any benefit (Barsanti and others 1982).…”
Section: Clinical Approachmentioning
confidence: 99%
“…In the single experimental study investigating urethral pressures in 6 anesthetized male cats with naturally occurring UO, investigators found that baseline urethral pressures following urinary catheter placement were not significantly different from control cats, which suggests that urethral spasm (or increased urethral pressure) plays a minor role in the pathogenesis of the UO . However, in a more recent report that evaluated anesthetized female cats, maximal urethral closure pressures in both the skeletal and smooth muscle portions of the urethra were higher in cats with a history of idiopathic cystitis compared to historical controls . This led the study investigators to conclude that the use of α‐1 antagonists and/or skeletal muscle relaxants may be useful in the prevention of UO if their study results were directly translatable to male cats with lower urinary tract disease …”
Section: Introductionmentioning
confidence: 99%
“…9 This led the study investigators to conclude that the use of ␣-1 antagonists and/or skeletal muscle relaxants may be useful in the prevention of UO if their study results were directly translatable to male cats with lower urinary tract disease. 9 Recently, several reports have evaluated risk factors for rUO in cats. In one retrospective study, 10 the administration of prazosin rather than phenoxybenzamine was associated with a reduced rUO rate.…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral, urodynamic, and/or electrophysiological techniques have been used for understanding LUT physiology and pharmacology in conscious [48], alpha chloralose-anesthetized [919], normal adult [9,17,2023] and neonatal cats [6,24]. Models of overactive bladder (OAB) [8,11,25,26], stress urinary incontinence (SUI) [10,27], spinal cord injury [7,2830], and interstitial cystitis [18,31] have also been developed and/or studied in the cat. Many acute OAB [8,11,25,26] and SUI [10,27] models frequently employ bladder irritation, commonly using dilute acetic acid (0.25-0.5%).…”
Section: Introductionmentioning
confidence: 99%